Perception of safety during the mammography exam:: contribution of humanized care - Adriana de Souza Medeiros Batista; Crissia Carem Paiva Fontainha; Talita Oliveira Santos; Luciana Batista Nogueira (Brazilian Journal of Radiation Sciences)
This article presents a discussion about the knowledge of the female population about breast cancer, the means presented by the Unified Health System (Sistema Único de Saúde – SUS) that contribute to the diagnosis and adherence to the early identification process. It was developed through semi-structured interviews about personal satisfaction with health and its relationship with advancing age, knowledge about breast cancer, risk factors, prevention, and diagnostic imaging. It involved women living in the city of Belo Horizonte, Minas Gerais and the metropolitan region. A total of 440 interviews were carried out in 2019, focusing on women over 40 years old. Most women said they had already had a mammography, and a minority had undergone treatment for breast cancer. General data on the characterization of the women interviewed are presented, as well as the perception of care promoted by public policies for women's health care.